Sea Ice Detection Using GNSS‐R Data From TechDemoSat‐1. Issue 8 (15th August 2019) - Cartwright, Jessica; Banks, Christopher J.; Srokosz, Meric
Abstract: A new method for the detection of sea ice using GNSS‐R (Global Navigation Satellite Systems Reflectometry) is presented and applied to 33 months of data from the U.K. TechDemoSat‐1 mission. This method of sea ice detection shows the potential for a future GNSS‐R polar mission, attaining an agreement of over 98% and 96% in the Antarctic and Arctic, respectively, when compared to the European Space Agency's Climate Change Initiative sea ice concentration product. The algorithm uses a combination of two parameters derived from the delay‐Doppler Maps to quantify the spread of power in delay and Doppler. Application of thresholds then allows sea ice to be distinguished from open water. Differences between the TechDemoSat‐1 sea ice detection and comparison data sets are explored. The results provide information on the seasonal and multiyear changes in sea ice distribution of the Arctic and Antarctic. Future potential and applications of this technique are discussed. Plain Language Summary: Monitoring of sea ice is essential in order to see the effects of a changing climate as well as understanding potential changes in the future. As a highly dynamic component of the cryosphere, sea ice plays an important role in these changes. Due to the remote nature and large area of sea ice, this must be performed through satellite observation in order to limit the spatial and temporal bias seen with in situ data. Presented is a novel technique for the detection of sea ice using GPS signals reflected from the ocean surface. A simple, low‐cost receiver picks up these signals from a spaceborne platform. In this case, data are collected from United Kingdom's TechDemoSat‐1 mission, which, although not designed for such measurements, gives excellent agreement with sea ice extent data from existing published sources. Key Points: Sea ice detection is presented from satellite GNSS‐R over the Arctic and Antarctic Sea ice presence is predicted based on multiple parameters across the first 33 months of data from U.K. TechDemoSat‐1 Results show excellent agreement with European Space Agency Climate Change Initiative sea ice product as well as other extent products